Efforts to Improve the Quality of Educators Through the Sima'an Program at the Ahlul Qur'an Tahfizh Educational Institution - Sari, Laila; Kustati, Martin; Gusmirawati, Gusmirawati (STIT Ahlussunnah Bukittinggi, 2025)
Improving the quality of educators is a very important aspect. This is because good quality educators will have an impact on the results and quality of learning that will be obtained. Therefore, efforts to improve the quality of educators must always be made in order to ensure the quality and success of a system. This study aims to determine the extent to which the sima'an program improves the quality of educators at the Ahlul Qur'an Tahfizh Education Institution. The sima'an program is an activity of listening to the recitation of the Quran on a regular basis by educators with the aim of improving the quality of reading, memorization, and pedagogical competence in tahfizh learning. This study used a qualitative method with a field study approach. The data collection techniques used were observation, interviews, and documentation. The results of the study found that the efforts made by the management of the Ahlul Qur'an Tahfizh Education Institution to improve the quality of educators through the sima'an program included planning and preparation of the sima'an program, implementation of the sima'an program, and evaluation of the sima'an program. In addition, the results of the study also show that the sima'an program has been proven effective in improving the quality of educators, both in terms of fluency in memorization, accuracy in makharijul huruf, tajwid, quantity of memorization, and others. Finally, this sima'an program can be used as a sustainable coaching strategy for Alquran memorization educators in order to improve the quality of education.